Characteristics of production methods of aluminium and magnesium matrix composite castings - Katarzyna Gawdzińska; Rafał Łapawa; Paweł Szymański; Artur Bejger; Krzysztof Nozdrzykowski (Advances in Mechanical and Materials Engineering, 2018)
Light metal (aluminium and magnesium) matrix composites in particular are being increasingly used in various kinds of transportation vehicles. The properties of final products are closely related to the employed production technology. This paper presents a brief review of the technologies used in aluminium and magnesium matrix composite casting, with a focus on the risks and benefits of each technology.